Analysis of results of use and interaction in higher level students when using a mobile collaborative learning application - Couoh Novelo, Miguel Ángel; Martin Interian, Nelly Sarahi (IE Revista de Investigación Educativa de la REDIECH, 2021)
Information and communication technologies are becoming increasingly important in education. This study aims to analyze the results of the use and interaction of students in a higher education institution when carrying out collaborative learning activities by contrasting between virtual and face-to-face work, to verify the feasibility of using a mobile application as a collaborative learning resource. A closed response survey was applied to 80 students of the Computer Engineering career in different semesters and subjects. The results show that the use of new virtual learning methods with higher-level students was a success, the application met the expectations of improving their performance according to the subject, as well as interacting collaboratively to have better results. In comparison between both modalities, the results of virtual work with the mobile application were superior than manual work in performance and interaction.